2007
DOI: 10.1016/j.atmosenv.2006.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl concentration estimates in the sunlit snowpack at Summit, Greenland

Abstract: Experiments were performed at Summit, Greenland (72134 0 N, 38129 0 W) to investigate hydroxyl mixing ratios in the sunlit surface snowpack (or firn). We added a carefully selected mixture of hydrocarbon gases (with a wide range of hydroxyl reactivities) to a UV and visible light transparent flow chamber containing undisturbed natural firn. The relative decrease in mixing ratios of these gases allowed estimation of the lower limit mixing ratio of hydroxyl radicals in the nearsurface firn pore spaces. Hydroxyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
1
19
2
Order By: Relevance
“…We note that modelled mean OH concentrations over the Arctic in August are around 5 -7 Â 10 5 molecules/cm 3 . This figure agrees with previous studies [e.g., Spivakovsky et al, 2000] and underlines that the Arctic cannot be neglected as an environment for oxidation in the summer, as has also been indicated by measurement studies [e.g., Beyersdorf et al, 2007].…”
Section: Effects Of Late Summer Sea-ice Removalsupporting
confidence: 82%
“…We note that modelled mean OH concentrations over the Arctic in August are around 5 -7 Â 10 5 molecules/cm 3 . This figure agrees with previous studies [e.g., Spivakovsky et al, 2000] and underlines that the Arctic cannot be neglected as an environment for oxidation in the summer, as has also been indicated by measurement studies [e.g., Beyersdorf et al, 2007].…”
Section: Effects Of Late Summer Sea-ice Removalsupporting
confidence: 82%
“…This behavior could imply that a chemical sink in the upper snow layers may contribute to the loss of these compounds. A series of recent investigations Beyersdorf et al 2007;France et al 2007) have pointed out the significant oxidation potential of sunlit snow. These studies demonstrated heterogeneous production of the hydroxyl radical from snow impurities, with hydrogen peroxide and nitrate being important substrates for this radical formation.…”
Section: Uptake Fluxesmentioning
confidence: 98%
“…O 3 deposition to snow and concentrations inside the snowpack has been found to be low (Zeller and Hehn, 1995;Helmig et al, 2009b;Bocquet et al, 2011). OH concentrations may be higher under sunny conditions (Anastasio et al, 2007;Beyersdorf et al, 2007), however, light levels on boreal forest floor during winter are very low. Thus, for oxidative reactions the snow-air interface, including the top layers of the snowpack, seems to be more important than the deeper layers of the snowpack.…”
Section: Sources and Sinks Of Snowpack Vocsmentioning
confidence: 99%
“…However, as discussed already in Sect. 4.2, the concentrations of the main oxidants, OH and O 3 , inside the snowpack are presumably low, except for the surface layer of the snowpack (Zeller and Hehn, 1995;Anastasio et al, 2007;Beyersdorf et al, 2007), as are the temperature and light levels, all of which reduce the reactivity of VOCs.…”
Section: Voc Fluxesmentioning
confidence: 99%